Efficacy of early treatment in patients with cobalamin C disease identified by newborn screening: a 16-year experience - Ahrens-Nicklas, Rebecca C. (Genet Med, 2017)
PURPOSE: Despite implementation of newborn screening (NBS), outcomes in cobalamin C disease (cblC) remain poor. Therapy with hydroxycobalamin and betaine is widely used, but dietary recommendations vary among metabolic centers. We present a longitudinal analysis of the relationship between metabolic control, diet, and outcomes in a cohort of cblC patients. METHODS: We completed a retrospective analysis of 12 patients with cblC referred for abnormal NBS results and followed in our center between 1999 and 2015. RESULTS: Of the patients, 87.5% had intellectual disability and 75% had retinopathy; 16.7% had one episode of mild acidosis. However, no patients manifested major metabolic decompensation. Developmental outcomes correlated more closely with initial metabolic abnormalities than with long-term metabolic control. Increased intake of medical foods resulted in better control but also perturbations in the ratios of essential amino acids and lower z-scores for head circumference. We found no relationship between diet and cognitive outcomes. CONCLUSIONS: Although dietary therapy for cblC patients improves metabolic control, few patients experience metabolic decompensation regardless of diet. Increased incomplete protein intake is not correlated with improvements in outcomes. Overall, outcomes are poor despite early initiation of therapy and regardless of the dietary strategy used.